Mobile Money and African Banking System - Li, Siqi (International Journal of Global Economics and Management, 2024)
With the development of financial technology, there has been a new payment method, that is, without a bank card, only a SIM card can be used through mobile phones for bank transfers and remittances, which is called mobile money. The rise and popularity of mobile money in various African countries is worthy of our attention because Africa is the region with the highest rate of mobile money usage. So, what kind of impact will the rise of mobile money have on the development of local mobile banks? We need to find out. Whether mobile money has become a competitor of mobile banks, we need to analyze through empirical analysis.